2003
DOI: 10.1046/j.1468-1293.2003.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

TRIZAL study: switching from successful HAART to TrizivirTM (abacavir‐lamivudine‐zidovudine combination tablet): 48 weeks efficacy, safety and adherence results

Abstract: Switching to Trizivir offers a potent and simplified regimen with equivalent efficacy and significant improvement in lipid abnormalities compared to continued triple therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 16 publications
(28 reference statements)
2
39
0
Order By: Relevance
“…Our results are consistent with other published data such as the Time Study and the ESS40013 Study where patients received maintenance therapy with Trizivir ® for 1 year or 6 months. 6,7 Persistance of controlled viremia was also observed in other switch studies with Trizivir ® , [8][9][10][11] but with shorter follow-up and no viral DNA evaluation. In our study, we observed no rebound of total cellular viral DNA under treatment simplification.…”
mentioning
confidence: 60%
“…Our results are consistent with other published data such as the Time Study and the ESS40013 Study where patients received maintenance therapy with Trizivir ® for 1 year or 6 months. 6,7 Persistance of controlled viremia was also observed in other switch studies with Trizivir ® , [8][9][10][11] but with shorter follow-up and no viral DNA evaluation. In our study, we observed no rebound of total cellular viral DNA under treatment simplification.…”
mentioning
confidence: 60%
“…22 Earlier studies addressing a switch to triple NRTI included patients who had not been ART-naïve from the start, resulting in suboptimal responses. 17,21,[23][24][25][26][27] Subsequent studies exploring the induction-maintenance concept in ART-naïve patients showed similar virologic success (i.e., noninferiority) for triple NRTI regimens compared to two-class cART. 16,21,22,[28][29][30][31] However, some of these studies were not entirely prospective, 16,21,29 or did not have a comparative design for the maintenance phase, 28,30 or used poorly tolerated quadruple regimens as induction regimens.…”
Section: (Panel On Antiretroviral Guidelines For Adult Andmentioning
confidence: 99%
“…Most studies reported improvements in lipids [63,[69][70][71][72]74,75], with decreases ranging from 8 to 25% for total cholesterol and 10 to 39% for triglycerides. Switching protease inhibitor to ABC also increased the incidence of virological failure, however, which may be explained by the lack of potency observed with the use of early NRTIonly ART regimens and new adverse reactions, including abacavir hypersensitivity.…”
Section: Antiretroviral Switch Strategies For Dyslipidaemiamentioning
confidence: 99%